2022
DOI: 10.2196/28885
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Ownership and Use Among Women Screening for Cervical Cancer in a Community-Based Setting in Western Kenya: Observational Study

Abstract: Background Mobile phone ownership among women of reproductive age in western Kenya is not well described, and our understanding of its link with care-seeking behaviors is nascent. Understanding access to and use of mobile phones among this population as well as willingness to participate in mobile health interventions are important in improving and more effectively implementing mobile health strategies. Objective This study aims to describe patterns of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although the community strategy was involved in creating awareness and supporting self-sample collection, other approaches such as use of mobile platforms to reach the targeted population and create awareness were not deployed and/or sustained during the pilot. A study in Kenya found that >70% of women reported ownership and daily use of a mobile phone, and 60% indicated that they would be comfortable receiving results via text messaging [ 27 ]. Another explanation could be logistical challenges, that caused periodic stock-outs of HPV testing commodities in some centers during the pilot.…”
Section: Discussionmentioning
confidence: 99%
“…Although the community strategy was involved in creating awareness and supporting self-sample collection, other approaches such as use of mobile platforms to reach the targeted population and create awareness were not deployed and/or sustained during the pilot. A study in Kenya found that >70% of women reported ownership and daily use of a mobile phone, and 60% indicated that they would be comfortable receiving results via text messaging [ 27 ]. Another explanation could be logistical challenges, that caused periodic stock-outs of HPV testing commodities in some centers during the pilot.…”
Section: Discussionmentioning
confidence: 99%
“…(22,23) As part of a trial of implementation strategies for cervical cancer screening, our team introduced text messaging to deliver HPV test results and follow-up plans to women screened in western Kenya. (24,25) We found that while this was a popular and e cient method of results delivery, it did not result in higher rates of treatment uptake when compared with noti cation through phone calls or home visits. From individual interviews at the time of treatment, we found that women wanted more clear and personalized information when receiving their results.…”
Section: Introductionmentioning
confidence: 93%
“…As part of a two-phase trial of implementation strategies for cervical cancer screening in western Kenya, our team introduced text messaging to deliver HPV test results and follow-up plans to women [ 24 , 25 ]. In the first phase, while text messaging was a popular and efficient method of results delivery, it did not result in higher rates of treatment uptake when compared with notification through phone calls or home visits.…”
Section: Introductionmentioning
confidence: 99%